Use of Mobile Technologies in Tourism: Natural Health Resorts Study - Brumen, BoÅ¡tjan; Planinc, Peter; Å pindler, Tomi; Gorenak, Mitja; Å tuhec, Tanja LeÅ¡nik (Mediterranean Journal of Social Sciences, 2020)
Mobile technologies have drastically changed the way people do everyday activities. Tasks previously reserved for desktop environments have moved to mobile devices, and nowadays, half of the internet traffic is stemming from mobile devices. The tourism industry is no exempt from the shift from desktop to mobile. In our research, we check to what extent natural health resorts have adapted and integrated mobile solutions to their websites. We collected data about the friendliness of selected websites using automated online tools and carried out a heuristic evaluation. The results were statistically analyzed and compared. Only roughly half of natural health resorts have optimized their websites for mobile devices. There are no statistically significant differences when comparing purely technical aspects. However, an in-depth heuristic evaluation has shown that some web sites are significantly more mobile-friendly than others and offer better technical conditions for enhanced user experience. Our study is the first technical and contentual evaluation of website mobile devices' friendliness in the natural health resort sector. It warns management, their marketing consultants, and web site developers about the opportunities they are missing by not supporting mobile users sufficiently. Further, it outlines deficiencies and provides suggestions and instructions for optimizing websites to enhance user-friendliness on mobile devices.